2023
DOI: 10.3390/ma16020610
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Optical Properties of CH3NH3PbX3 (X = Br, I) Single Crystals Using Terahertz Time-Domain Spectroscopy

Abstract: Organometallic lead bromide and iodide perovskite single crystals (PSCs) are potential candidates for terahertz applications. Herein, we performed terahertz time-domain spectroscopy (THz-TDS) in the frequency range of 0.1–3.0 THz on different thicknesses of MAPbBr3 (0.3, 0.6, and 0.8 mm) and MAPbI3 (0.6, 0.8, 0.9, 1.3, and 2.3 mm). The measurements were carried out with respect to the position (along the focal area), azimuthal rotation of the PSCs, and incidence angles of the reference THz pulse on the PSCs’ s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…Figure 2b presents the XRD results of MAPbBr3 SCs with the passivation of different Zn-PP weight percentages. The results indicate that there are four main diffraction peaks for the reference sample, as shown in Figure 2b, which appeared at around 15.78, 30.94, 46.64, and 63.31 and were related to [100], [200], [300], and [400] crystal planes, respectively, which confirmed that all the MAPbBr3 single crystals possessed cubic crystal structure, as reported previously by different groups [27][28][29][30]. Furthermore, the absence of discernible impurity peaks in the results obtained from the pristine MAPbBr3 single crystals suggests the high purity of the crystals grown via the ITC method.…”
Section: Resultssupporting
confidence: 85%
“…Figure 2b presents the XRD results of MAPbBr3 SCs with the passivation of different Zn-PP weight percentages. The results indicate that there are four main diffraction peaks for the reference sample, as shown in Figure 2b, which appeared at around 15.78, 30.94, 46.64, and 63.31 and were related to [100], [200], [300], and [400] crystal planes, respectively, which confirmed that all the MAPbBr3 single crystals possessed cubic crystal structure, as reported previously by different groups [27][28][29][30]. Furthermore, the absence of discernible impurity peaks in the results obtained from the pristine MAPbBr3 single crystals suggests the high purity of the crystals grown via the ITC method.…”
Section: Resultssupporting
confidence: 85%
“…In this study, the characterization and prediction of the photothermal aging degree of PE pipes for outdoor use were studied based on terahertz time-domain spectroscopy [ 13 , 14 ]. Firstly, aging samples of the PE pipes were simulated and manufactured.…”
Section: Introductionmentioning
confidence: 99%